Career guidance in information professional / Nur Atiqa Saleh, Nurul Aida Jamil and Fatin Eleena Sha 'mar - Saleh, Nur Atiqa; Jamil, Nurul Aida; Sha 'mar, Fatin Eleena (Faculty of Information Management, 2015)
According to Allport, . (1961) said what is information professional? An Information professional is person who systematically uses information to do his / her task to advance the mission of the organization. Information professional accomplishes this through the development, deployment and management of information resources and services. In addition, the information professional harnesses technology as a critical tool to accomplish goals. Information Professional's not limited to knowledge managers, chief information officers, information brokers, consultants and others. Information professional can be librarian, archivist and web system developers. Universities around the world has offered course in Library and Information Science in academic degrees. In Malaysia, there are few universities such as University of Selangor Unisel), International Islamic University Malaysia (HUM), and Universiti Teknologi Mara (UiTM) which has offered this course and can leas students to become an information professional. It related in few subjects such as library studies, archival studies, information systems, information management and record management. The discussion below shows some career guidance for those students who take Information Management as their course studies.